Nuclear magnetic resonance relaxation efficiency of composite magnetic nanoparticles MgxZnyFe3–x–yO4 / polyelectrolyte shell for medical diagnostics - Shutava, Tatsiana G.; Pankov, Vladimir V.; Livanovich, Kanstantsin S.; Kotsikau, Dzmitry A.; Petrova Еlena G.; Natarov, Valentin O.; Bogachev, Yury V.; Nikitina, Anastasiya V.; Kostina, Aleksandra A.; Sabitova, Viktoriya A. (Journal of the Belarusian State University. Chemistry, 2017)
Nuclear magnetic resonance relaxation of protons in aqueous solutions of MgxZnyFe3 – x – yO4 ferrite nanoparticles, on the surface of which poly(diallyldimethylammonium chloride) is adsorbed, has been investigated. It was shown that the transverse relaxivity r2 is significantly higher than the longitudinal relaxivity r1 and depends on the composition and synthetic method of ferrites. Being of comparable sizes, MgxZnyFe3 – x – yO4 nanoparticles synthesized with carbonate possess higher values of r2 and r1 as compared with ferrites obtained by coprecipitation with base. It was concluded that magnetic nanoparticles stabilized with a polyelectrolyte shell can be used in development of negative contrast agents for magnetic resonance imaging diagnostics.